Checklist of decapod crustaceans from the coast of the So Paulo state (Brazil) supported by integrative molecular and morphological data: V. Dendrobranchiata and Pleocyemata [Achelata, Astacidea, Axiidea, Caridea (Alpheoidea and Processoidea excluded), Gebiidea, Stenopodidea - Mantelatto, Fernando L.; Tamburus, Ana F.; Carvalho-Batista, Abner; Rossi, Natalia; Buranelli, Raquel C.; Pantaleo, Joo A F; Teles, Jeniffer N.; Zara, Fernando J. [UNESP]; Carvalho, Fabricio L.; Bochini, Gabriel L.; Terossi, Mariana; Robles, Rafael; et al. (Magnolia Press, 2022)
This checklist is the fifth and last compilation on the decapod crustaceans reported to So Paulo (Brazil) coastal area, resulting from long-term multidisciplinary projects, which combined morphological analyses and molecular techniques. The current research includes 75 decapod species, herein referred as shrimps/lobsters-like (shrimps, ghost-shrimps, lobsters, and related groups), reported to So Paulo coastal area. These species occur in marine, estuarine, and amphidromous habitats and are classified into 21 families as follow: Aristeidae (2 spp., 2 genera), Atyidae (4 spp., 2 genera), Axianassidae (1 sp., 1 genus), Callianassidae (1 sp., 1 genus), Callichiridae (6 spp., 4 genera), Crangonidae (1 sp., 1 genus), Glyphocrangonidae (1 sp., 1 genus), Luciferidae (2 spp., 2 genera), Nephropidae (4 spp., 2 genera), Palaemonidae (15 spp., 9 genera), Palinuridae (2 spp., 1 genus), Pandalidae (1 sp., 1 genus), Pasiphaeidae (1 sp., 1 genus), Penaeidae (10 spp., 6 genera), Sergestidae (3 spp., 3 genera), Sicyoniidae (4 spp., 1 genus), Scyllaridae (5 spp., 3 genera), Solenoceridae (4 spp., 3 genera), Stenopodidae (2 spp., 1 genus), and Upogebiidae (6 spp., 1 genus). We generated new sequences of cytochrome oxidase subunit I (barcode region) and 16S genes (51 and 54, respectively) of 54 species. Our examination concluded that 75 shrimps/lobsters-like species are reported to the So Paulo coast. We excluded Leander tenuicornis (Palaemonidae), Penaeus setiferus (Penaeidae), Philocheras gorei (Crangonidae), and Rhynchocinetes typus (Rhynchocinetidae) from this list.